Theoretical Review Of The Group Guidance Model With The Muhasabah Approach To Increase Relijiusity - Meyla Tessi Karyati; Zubaidah Zubaidah; Garik Petoukhoff; Jessica Papaioannou (Yayasan Minang Darussalam, 2022)
Guidance counseling teachers in schools are required to have insights and skills related to group guidance, including various theories of group guidance researched by researchers in the field of guidance and counseling to improve various psocological aspects. One of the very important psychological aspects in life is religiosity. The purpose of this study is to formulate a group guidance model with a muhasabah approach to improve religiosity. This research method uses the study of your literate. Data are collected from reference books, journals, proceedings and reports of research results. Analisis data through contentanalysis techniques which are then described and balanced by researchers. The results showed that the group Guidance modelwith the Muhasabah Approach (BKp-M model) is one of the guidance models and consesualling through integrative and interconnective group guidance services with the muhasabah approach by utilizing group dynamics to facilitate optimal and comprehensive individual development in various aspects of development individual self to face the challenges of change in life. The research method is a literature review. Data is obtained through various analysis of books, journals and proceedings. Data analysis through content analysis. The results showed that group guidance of the muhasabah approach can be used to improve religion. For various parties who want to increase religiosity can use the guidance of the muhasabah approach group. Likewise, for subsequent researchers, they can use this theoretical data to be experimented with